MODEL PENURUNAN KETIDAKRATAAN PADA PERKERASAN LENTUR - Neni Kusnianti; Siegfried - (Jurnal Jalan-Jembatan, 2019)
ABSTRACT In pavement management system, the roughness deterioration model is an important parameter to determine the functional performance in the future. The information of functional and structural performances will set the type of maintenance needed during the analysis period. The general model of roughness deterioration is a combination of some road deffect models such as crack, rutting, and pothole, and this seems a bit complicated. To apply this model, it needs a quite huge data and this will cause to the cost of data collection and equipment used. Because of lack of equipment and to make more efficient, it needs to adopt a simpler model of roughness deterioration. The aggregate model of roughness deterioration is a simple model used in many African countries that is a function of structural strength, environmental factor, and traffic. By adopting this model, it needs a simple calibration by comparing the results of this model to that of HDM4 program which have been applied in some countries like Ghana, Brazilia, Phillipines and Malaysia. The result shows that the roughness values of these two methods are not significantly different especially for the IRI less than 12. This means that the aggregate model of roughness deterioration is acceptable to use in Indonesia, because generally the Indonesian pavement management system suggest that the IRI of 12 will require reconstruction. Keywords: IRI, model of roughness deterioration, pavement management system, aggregate mode of roughness deterioration, HDM